DIRECT VS INDIRECT CORRECTIVE FEEDBACK FOR WRITING IMPROVEMENT: STUDENTSâ€™ PREFERENCES - Abidah, Khilda Husnia; Ratih, Elisa (Universitas Wiralodra, 2022)
This research presents the studentsâ€™ preference for feedback in deciding what specific feedback will be valuable and positively affect the studentsâ€™ writing performance. There might be a mismatch between studentsâ€™ preferences and lecturerâ€™s practice from a few past studies. A quantitative research design was utilized in this study. It was conducted in Muhammadiyah Malang University with 70 English Language Education Department students as the participants. A data set of 10 questions in the survey for students was adjusted from Aridah et al. (2017). Further, the data were scored using the â€œFeedback Scaleâ€ with a scale ranging from 0 to 1. The finding showed that the feedback preference of the students is direct corrective feedback, in which the mean score was higher (M=6.53) than indirect corrective feedback. The students believed that direct corrective feedback gave more additional clearness. Therefore, this study recommended that the lecturer give feedback based on the studentsâ€™ preference which is direct corrective feedback to improve their writing skills easily and effectively.